APPLICATION OF PRENATAL GENTLE YOGA EXERCISES FOR PRIMIGRAVIDA PREGNANT WOMEN IN TRIMESTER III - anggraini, desy (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2025)
Background : A process of pregnancy experienced by every woman where women will go through many processes of change ranging from physical and psychological changes, changes will continue to occur until the pregnant woman is about to give birth. This condition will always cause physical discomfort for pregnant women, shadows about the birth process, etc. Shadows like that are common in pregnant women who are about to give birth. Conditions like that can cause feelings of anxiety in pregnant women, especially in women who are pregnant for the first time (Primigravida). An effective way to deal with problems related to the high mortality rate of pregnant women and the morbidity of pregnant women triggered by anxiety is to do physical exercise, such as walking, water exercise, and prenatal yoga. Prenatal yoga is a modification of classical yoga that has been adapted to the condition of pregnant women, which is carried out with a softer and slower intensity. Objective: To find out the true description of the effect of the application of prenatal yoga exercises on the anxiety of third trimester primigravida pregnant women. Methods / Design in this study is a narrative study using a literature study that describes the correct application of prenatal yoga practice to decrease anxiety levels. Research Results: The research results used consisted of 5 articles published online between 2018-2020. Based on these 5 articles, the correct application of prenatal yoga exercises can overcome anxiety in third trimester primigravida pregnant women. Conclusion: the application of good and correct prenatal yoga can overcome the anxiety level of primigravida pregnant women and also affect the incidence of pregnancy anxiety in third trimester primigravida pregnant women.